Pelos céus e pela terra: a conquista de Maiorca (1229) como legitimidade do Rei Jaime I, o Conquistador (1208-1276) - Viana, Luciano José (2009)
In this work we analyze the narrative of the conquest of Majorca in 1229, the first big conquest in the Book of Deeds of James I, the Conqueror. We start from the hypothesis that Jaime I narrated in his memories this arms achievement to legitimize himself in front of his noble opponents and also to affirm himself as prosecutor of Barcelona count´s line. First, we decided to examine the moments before the conquest, given in chapters 1 to 46 of the Book of Deeds, where we find the first experiences of Jaime I as a natural king, feudal king and knight king. Afterwards, we analyze the narrative about the conquest of Majorca in chapters 47 to 106 of the Book of Deeds; this is the main part of our work because it´s in there where the king uses his victory to legitimize himself. As theoretical and methodological apparatus we used the hermeneutical method of Hans-Georg Gadamer.